Incidencia del acoso escolar en la inteligencia emocional de los estudiantes comprendidos en edades de 10 a 14 años de la escuela de Educación General Básica IV Centenario, periodo 2015-2016. - Pineda Rodríguez, Carlos Ángel (2016)
Bullying constitutes a social phenomenon that affects all students, especially the Mental Health of victims and aggressors, and by implication impairs the integral development of human capacities, including the capacity for Emotional Intelligence. This research work named: "INCIDENCE OF BULLYING IN THE EMOTIONAL INTELLIGENCE OF THE STUDENTS UNDERTAKEN IN AGES OF 10 TO 14 YEARS AT “IV CENTENARIO” SCHOOL FROM THE CITY OF LOJA, PERIOD 2015-2016" It concerns directly with the profile, professional practice and with some of the occupational fields of the Clinical Psychologist. The research was based on a multidimensional study, whose general objective was to determine the incidence of Bullying in Emotional Intelligence of students between the ages of 10 and 14 years; And, the specific objectives were: -To investigate cases of School Harassment. - Identify the level of Emotional Intelligence of all students; - To relate the incidence of Bullying with the level of Emotional Intelligence and finally, - To develop a Psychotherapeutic Plan as an alternative solutions to the met problem. The research process was based on the construction of the research project, execution of the field work through the application of psychometric instruments and elaboration of the final report. In this study, the Descriptive-Transversal method was used, in which a sample of 150 students was selected: 112 of the men and 38 women. After that, the Preconceptions Questionnaire of Intimidation and Abuse among Equals, adapted by José María Avilés Martínez (2002) to evaluate Bullying and the Hendrie Weisinger Emotional Intelligence Test (2001) were applied with the objective of evaluating the level of Emotional Intelligence and its indicators. Consequently, the results achieved led to the following conclusions: - There is a high rate of Bullying, which occurs in all its manifestations, both verbal, physical, and social, respectively. - There is no direct relationship between the variables since the students evaluated, both victims and non-victims of Bullying, mostly present a significantly low level of Emotional Intelligence, manifesting itself with the following characteristics: insecurity and lack of self-confidence, Conflicts in the recognition and control of their emotions, low capacity for self-motivation, problems to relate to others, and low capacity for emotional counseling. This significantly low level has as main cause, the incidence of Bullying, which some students are victims. This was useful to the elaboration of a Psychotherapeutic Plan as an alternative proposal, in which psychotherapeutic and psychopedagogical processes are integrated, with the purpose of offering strategies to improve intra-extra school relationships and the quality of emotional intelligence, since it will strength as an optimal element for the resolution of problems in general and the achievement of a school coexistence. Key words: Bullying or Bullying, Emotional Intelligence, Emotional Intelligence Levels, Emotional Intelligence Indicators, Psychotherapeutic Plan.